Pergeseran Dalam Penerjemahan Proklamasi Kemerdekaan Indonesia Dalam A History Of Modern Indonesia Since C.1200 Karya Ricklefs - Nugraha, Anandika Panca (Kementerian Sekretariat Negara Republik Indonesia, 2016)
This article attempts to investigate the shifts in translating the Proclamation of Indonesian Independence in M.C. Ricklefs’ book entitled A History of Modern Indonesia since c.1200. This descriptive qualitative research uses Catford’s translation shifts and Vinay and Darbelnet’s taxonomy of translation shifts as the theoretical groundwork in identifying the shifts and then analyzing their impact on the translation of the Proclamation text. After comparing the original and Ricklefs’ translation, this research finds16 shifts out of 19 pairs of units of translation including modulation, level shift, class shift or transposition, unit or rank shift, structural shift, equivalence, and adaptation. These shifts lead to a slight change in the text’s formality. Research in translation shifts is potentially biased since there are no clear-cut boundaries of units of translation. As this article uses units of translation at the word and phrase levels, further research can be conducted by considering more complex units. Key words: unit of translation, translation shift, translation, procedures, legal text.